2021
DOI: 10.3390/ijms22094845
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Modification of Waxy to Genetically Improve Starch Quality in Rice Grain

Abstract: The waxy (Wx) gene, encoding the granule-bound starch synthase (GBSS), is responsible for amylose biosynthesis and plays a crucial role in defining eating and cooking quality. The waxy locus controls both the non-waxy and waxy rice phenotypes. Rice starch can be altered into various forms by either reducing or increasing the amylose content, depending on consumer preference and region. Low-amylose rice is preferred by consumers because of its softness and sticky appearance. A better way of improving crops othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 172 publications
(377 reference statements)
0
15
0
Order By: Relevance
“…Starch content and starch-related proteins are prominent in wheat grain; PTMs involved in starch quality have been reviewed (80). Our study lists numerous potential PTMs; this warrants more experiments to validate them and decipher their role in LMA response.…”
Section: A Non-redundant Wheat Database To Annotate Lc-ms2 Results An...mentioning
confidence: 85%
“…Starch content and starch-related proteins are prominent in wheat grain; PTMs involved in starch quality have been reviewed (80). Our study lists numerous potential PTMs; this warrants more experiments to validate them and decipher their role in LMA response.…”
Section: A Non-redundant Wheat Database To Annotate Lc-ms2 Results An...mentioning
confidence: 85%
“…Figure 2 shows starch biosynthesis and mutants of important starch synthesis enzymes. The post-translational modification of these enzymes through phosphorylation, alternative splicing, and allosteric changes plays a vital role in modifying starch content and altering the amylose–amylopectin composition ( Huang et al., 2020b ; Adegoke et al., 2021 ). Table 1 shows various mutants with altered physicochemical properties.…”
Section: Genetic Basis Of Rice Ecq Improvementmentioning
confidence: 99%
“…In rice ECQ improvement, targeted gene silencing is an effective tool to manipulate biosynthetic pathways in a constitutive or tissue-specific manner to obtain the desired phenotype. For example, the Wx , SSI , SSII-2 , ALK , FAD2-1 , and Badh2 genes were suppressed by RNA interference, and the resulting transgenic rice showed improved ECQ traits compared with the wild type ( Li et al., 2018a ; Zhao et al., 2019 ; Chen et al., 2020 ; Adegoke et al., 2021 ). However, widespread adoption of transgenic crops carrying foreign genes faces roadblocks due to regulatory concerns about potential toxicity and allergenicity to humans, adverse effects on non-target organisms, evolution of resistant weeds and insects, and so forth.…”
Section: Modern Molecular Breeding Strategies For Rice Ecq Improvementmentioning
confidence: 99%
“…In previous studies on some dark endosperm mutant rice, it is found that some low enzymatic activity natural mutations or genetically modified low enzymatic activity proteins of GBSSI caused the rice to exhibit a translucent phenotype due to the synthesis of less amylose (below 13%). This suggests a direct correlation between GBSSI and rice transparency [36][37][38]. Zhang et al studied transgenic rice lines with GBSSI activity and found that AC was lower in rice lines with lower GBSSI activity, and the grains showed a milky opaque appearance.…”
Section: Appearance Quality-associated Starch-regulated Genesmentioning
confidence: 99%